A current perspective of canstatin, a fragment of type IV collagen alpha 2 chain - Muneyoshi Okada; Hideyuki Yamawaki (Elsevier, 2019)
Type IV collagen is a main component of basement membrane extracellular matrix. Canstatin, a non-collagenous C-terminal fragment of type IV collagen α2 chain, was firstly identified as an endogenous anti-angiogenic and anti-tumor factor, which also has an anti-lymphangiogenic effect. Then, canstatin has been widely investigated as a novel target molecule for cancer therapy. The anti-angiogenic effect of canstatin may be also useful for the treatment of ocular neovascularization. Recently, we have demonstrated that canstatin, which is abundantly expressed in the heart tissue, exerts various biological activities in cardiac cells. In rat H9c2 cardiomyoblasts, canstatin inhibits isoproterenol- or hypoxia-induced apoptosis. Canstatin plays an important role in modulating voltage-dependent calcium channel activity in rat cardiomyocytes. Canstatin also regulates various biological functions in rat cardiac fibroblasts and myofibroblasts. The expression of canstatin decreases in the infarcted area after myocardial infarction. This review focuses on a current perspective for the roles of canstatin in tumorigenesis, ocular neovascularization and cardiac pathology. Keywords: Anti-tumor effect, Canstatin, Fibroblasts, Cytoprotective effect, Myocardial infarction